"See Media": Coco Fusco's Direct Address and the Performance of In/Security. (1st October 2016) - Sparling Williams, Stephanie
Abstract: A Room of One's Own: Women and Power in the New America (2006 – 2008) is a multi-media performance art piece by visual artist Coco Fusco. In a lecture style performance staged at the Museum of Modern Art (MoMA) as part of their 2007 symposium The Feminist Future: Theory and Practice in the Visual Arts, Fusco explores the use of women in US military interrogation efforts during the height of the War on Terror and – problematic and violent as it may be – mounts a parallel attack against the art world itself. Although invited to speak, Fusco speaks (performs) out of turn – and out of sync in order to level a critique at the very establishment in which the symposium was held. In doing so, Fusco directs our attention towards the interwoven workings of power, surveillance, silence, and the making and the performances of particular kinds of citizen/subjects/enemy combatants/art objects/interrogators/artists. This article seeks to address how visual culture and US military security discourses are inextricably linked through interwoven histories and unsettling relationships between race and national security, national security and feminism, as well as race and feminism.